The level of emotional inteligence in women's volleyball team - Roskova, M.; Bendikova, E. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2012)
In our research we have analyzed the structure and cooperation within women`s volleyball team on the basis of emotionalism and communication level. We have analyzed the quality of relationships in this team on the basis of a test aimed at positive self-concept and cogitation, emotional resistance, emotional potential for sport, ways of performance and solving conflicts. According to the test, we have concluded that their quality of relationships alongside other aspects indirectly affect the performance of the team.